Linkages between supplier, customer involvement and business performance: A green supply chain investigation in the poultry industry - Ariffin, Ahmad Shabudin; Lamsali, Hendrik; Mohtar, Shahimi (2012)
The aim of this study is to propose an investigation over the potential relationships between supplier and customer involvement towards business performance in poultry production. The potential role of employees' skill levels as moderating variable between the aforementioned independent and the defendant variables are discussed. Green supply chain practices and its corresponding performance indicators in the form of poultry waste management are among the important measures in the defendant variable (business performance).Based on the extensive survey of relevant literature, a research framework is then proposed. The inclusion of customer involvement (independent variable), the skill levels (moderating variable) and green supply chain practices (dependent variable) in the proposed framework is the main contribution of this study. It is expected that this study will be beneficial to poultry industry, relevant policy makers and the growing body of knowledge of supply chain investigation in the agribusiness.